Sitting Posture Amongst Level One Primary Schoolchildren (Lops) In Perlis, Kedah And Pulau Pinang - Masyidah M. I., Wahyuni; M. K., Noor Azlina; Z., Muhammad Fauzi (2016)

(untitled)
This study is a continuous study of previous paper ( Wahyuni Masyidah, Noor Azlina & Muhammad Fauzi 2015). Based on the quantitative result of mismatch between anthropometric and chair dimensions amongst LOPS show that over 96% did not fit to school chair dimension during learning session in the class, and only 4% were fitted to the school chair in class. Due to the mismatch result, the aim of this paper is to reveal the qualitative result of the study which frequent types of sitting postures that attribute to discomfort that have been identified amongst Level One Primary Schoolchildren (LOPS) in Kedah Perlis and Pulau Pinang. The qualitative analysis consist 12 respondent that randomly been taken between 7 to 9 years old from different primary school in Perlis, Kedah and Pulau Pinang. It can be concluded that the sitting postures amongst LOPS could lead towards permanent damage to the body and jeopardize the children’s health.